Bergayuh Agar Tak Lumpuh: Proyeksi Peran ASEAN dalam Penyelesaian Isu Semenanjung Korea - Gaffar Mu’aqaffi; Hafrian Yusuf Ramdhani; Rizki Ananda; Ahmad Naufal Farras; Septian Wahyudi; Addafi Aryaguna (Universitas Diponegoro, 2018)
As a regional organization, ASEAN has responsibility to solve the problem in Korean Peninsula. ASEAN’s involvement in effort to solve the problem in Korean Peninsula can be seen by the existence of ARF. Besides ARF, ASEAN also has many cooperations with other parties-involved that can be exploited as an instrument to solve the problem. However, ASEAN’s involvement only limited to the providing forum (ARF) for the parties involved in the problem. The limitation of ASEAN is interesting to discuss since it proved to be fail to provide concrete outcome. This writtings try to find the reasons behind the inability of ASEAN to solve the problem. Specifically, this writtings use the concept of bandwagon to analyse the cause of the limitation. The main argument of this writing is the inability of ASEAN is caused by bandwagon behavior of ASEAN countries to great power that involved in this problem.Keywords: ASEAN, Korean Peninsula, bandwagon